Nonalcoholic Fatty Liver Disease and Cardiovascular Disease: Has the Time Come for Cardiologists to Be Hepatologists? - Ahmed, Mohamed H.; Barakat, Salma; Almobarak, Ahmed O. (Journal of Obesity, 2012)
Nonalcoholic fatty liver disease (NAFLD) is prevalent in people with the metabolic syndrome and type 2 diabetes and is present in up to one-third of the general population. Evidence is now accumulating that NAFLD is associated with obesity and diabetes and may serve as a predictor of cardiovascular disease (CVD). The possible mechanisms linking NAFLD and CVD include inflammation and oxidative stress, hyperlipidaemia, insulin resistance, and direct impact of NAFLD on coronary arteries and left ventricular dysfunction. In addition, several studies suggest that NAFLD is associated with high risk of CVD and atherosclerosis such as carotid artery wall thickness and lower endothelial flow-mediated vasodilation independently of classical risk factors and components of the metabolic syndrome. It is not yet clear how treatment of NAFLD will modulate the risk of CVD. Furthermore, studies are urgently needed to establish (i) the pathophysiology of CVD with NAFLD and (ii) the benefit of early diagnosis and treatment of CVD in patients with NAFLD. In the absence of biochemical markers, it is crucial that screening and surveillance strategies are adopted in clinical practice in the growing number of patients with NAFLD and at risk of developing CVD. Importantly, the current evidence suggest that statins are safe and effective treatment for CVD in individuals with NAFLD.